Method for the classification of tea diseases via weighted sampling and hierarchical classification learning - Li, Rujia; Qin, Weibo; He, Yiting; Li, Yadong; Ji, Rongbiao; Wu, Yehui; Chen, Jiaojiao; Yang, Jianping (International Journal of Agricultural and Biological Engineering, 2024)
This study proposed a weighted sampling hierarchical classification learning method based on an efficient backbone network model to address the problems of high costs, low accuracy, and time-consuming traditional tea disease recognition methods. This method enhances the feature extraction ability by conducting hierarchical classification learning based on the EfficientNet model, effectively alleviating the impact of high similarity between tea diseases on the model’s classification performance. To better solve the problem of few and unevenly distributed tea disease samples, this study introduced a weighted sampling scheme to optimize data processing, which not only alleviates the overfitting effect caused by too few sample data but also balances the probability of extracting imbalanced classification data. The experimental results show that the proposed method was significant in identifying both healthy tea leaves and four common leaf diseases of tea (tea algal spot disease, tea white spot disease, tea anthracnose disease, and tea leaf blight disease). After applying the “weighted sampling hierarchical classification learning method” to train 7 different efficient backbone networks, most of their accuracies have improved. The EfficientNet-B1 model proposed in this study achieved an accuracy rate of 99.21% after adopting this learning method, which is higher than EfficientNet-b2 (98.82%) and MobileNet-V3 (98.43%). In addition, to better apply the results of identifying tea diseases, this study developed a mini-program that operates on WeChat. Users can quickly obtain accurate identification results and corresponding disease descriptions and prevention methods through simple operations. This intelligent tool for identifying tea diseases can serve as an auxiliary tool for farmers, consumers, and related scientific researchers and has certain practical value. Keywords: tea diseases, hierarchical classification learning, weighted sampling, classification method, EfficientNet, mini-program DOI: 10.25165/j.ijabe.20241703.8236 Citation: Li R J, Qin W B, He Y T, Li Y D, Ji R B, Wu Y H, et al. Method for the classification of tea diseases via weighted sampling and hierarchical classification learning. Int J Agric & Biol Eng, 2024; 17(3): 211-221.